Long-term culture of canine peripheral blood monocytes in vitro. - Ho, C K (1979)
Various cultural conditions were assessed for their ability to maintain canine peripheral blood monocytes in vitro. Approximately ten days after incubation of peripheral blood leukocytes in Earle's minimum essential medium supplemented with homologous red cell lysates and normal horse serum, virtually a pure macrophage culture was obtained which could then be maintained for about two months. This culture was judged to be pure by surface marker analysis and their phagocytic activity. The number of monocytes could be increased by injecting the dogs with a chloroform extract from Listeria monocytogenes prior to collection of the blood.